Penerapan Metode Home Schooling pada Pendidikan Anak Usia Dini di Masa Pandemi Covid-19 - Yuanita Anton Sope (Indonesian Journal of Early Childhood: Jurnal Dunia Anak Usia Dini, 2022)
Homeschooling or home schooling is a phenomenal alternative education model that is widely discussed by the community, parents, and education practitioners. The homeschooling method is an option for parents for a variety of reasons.PAUD institutions and their ranks during the Covid-19 pandemic should consider the importance of increasing competence in carrying out learning activities during the Covid-19 pandemic where learning cannot be done face-to-face but is done online. Institutions and teachers are required to try various methods in the delivery of learning for the sake of the PAUD institution. The homeschooling method is one that can be used as a reference for PAUD institutions and teachers in carrying out distance learning.To be able to maintain the existence of PAUD institutions, PAUD institutions and teachers currently must be able to live in harmony with the Covid-19 pandemic starting from the delivery of learning and learning procedures, which currently must be more adapted and always focus on health procedures.In this paper, the author tries to provide an overview of how teachers can provide learning according to their obligations as educators and how parents can accept and convey it to their children and implement it in a fun way.